THE LITHUANIAN VERSION OF THE PARENTING STRESS INDEX (PSI): A PSYCHOMETRIC AND VALIDITY INVESTIGATION - Aidas Perminas; Evelina Viduoliene (European Scientific Journal, ESJ, 2013)
﻿It is important to have a valid measure of parenting stress in the Lithuanian language as parenting can be a problematic field of family life in Lithuania. According to the results of an international study dealing with 24 countries, Lithuania is the second country (and has the leading position in Europe) where parents have evaluated their children as having the most behavioral and emotional problems (Rescorla, Achenbach et al., 2011). The reliability, factor structure, concurrent and discriminant validity of the Parenting Stress Index (PSI, Abidin, 1995) was examined for 1228 mothers of children aged between 2.5 and 6 years. Methods: Parenting Stress Index, Child Behavior Checklist 1.5−5 (CBCL 1.5–5, Achenbach & Rescorla, 2000), Parenting Styles and Dimensions Questionnaire (PSDQ short form, Robinson et al., 2001). An exploratory factor analysis of the 13 PSI scales indicated that the original two−factor solution (Child and Parent characteristics domains) fits the data best. Concurrent and discriminant validity was supported. The Lithuanian version of the Parenting Stress Index is a valid and reliable measure for assessment of distress related to parenthood.